2016
DOI: 10.1108/prt-04-2015-0041
|View full text |Cite
|
Sign up to set email alerts
|

Double layer water-borne heat insulation coatings containing hollow glass microspheres (HGMs)

Abstract: Purpose This study aims to construct a double layer heat insulation coating based on hollow glass microspheres (HGMs) and to investigate the effect of particle size on barrier property and heat insulation performance. Design/methodology/approach The waterborne double layer coating was composed of an anticorrosive epoxy ester primer and an HGM-containing silicone acrylic topcoat. With varied HGM sizes (20 μm, 40 μm, 60 μm and a 1:3 w/w mixture of 20 and 60 μm particles), the coating was immersed in 3.5 wt% Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A cost-effective solution to reduce this energy waste consists in minimizing the solar heat load and the heat dispersion through the roof and walls by using insulator coating materials that have low thermal conductivity and high infrared radiation reflectivity [ 62 , 63 ]; multiple layer thermal insulation coatings may be the most effective solution [ 63 ]. The thermal characteristics of HGM have been the subject of several papers, where different aspects were investigated, such as the mechanism of heat transfer in HGM [ 64 , 65 ] or the effect of inclusion of HGM in different materials [ 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Figure 5 shows a typical scanning electron microscope (SEM) image of soda-lime silicate glass microbubbles fabricated by Sinosteel Maanshan New Material Technology (Maanshan, China) [ 64 ].…”
Section: Applications In the Field Of Energymentioning
confidence: 99%
See 1 more Smart Citation
“…A cost-effective solution to reduce this energy waste consists in minimizing the solar heat load and the heat dispersion through the roof and walls by using insulator coating materials that have low thermal conductivity and high infrared radiation reflectivity [ 62 , 63 ]; multiple layer thermal insulation coatings may be the most effective solution [ 63 ]. The thermal characteristics of HGM have been the subject of several papers, where different aspects were investigated, such as the mechanism of heat transfer in HGM [ 64 , 65 ] or the effect of inclusion of HGM in different materials [ 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Figure 5 shows a typical scanning electron microscope (SEM) image of soda-lime silicate glass microbubbles fabricated by Sinosteel Maanshan New Material Technology (Maanshan, China) [ 64 ].…”
Section: Applications In the Field Of Energymentioning
confidence: 99%
“…In the design of insulating structures, it is also important to investigate the long-term durability of the material as a function of different environmental parameters such as water, temperature, and pressure. As an example, Zhang et al [ 72 ] developed a double layer coating composed of an anticorrosive epoxy ester primer and an HGM-containing silicone acrylic topcoat. The HGM size must be properly selected to provide balanced performance on both anticorrosion and heat insulation.…”
Section: Applications In the Field Of Energymentioning
confidence: 99%
“…Due to the low density of GM and better interfacial bonding with silicone matrix, the addition of GM has a better improvement effect on specific tensile strength and elastic modulus compared to CM. Zhang et al 18 used epoxy resin as primer and HGM‐containing silicone acrylic as topcoat to prepare HGM‐based double‐layer thermal insulating coatings and investigated the effect of HGM particle size on the thermal insulating properties of the coatings. The results showed that the coatings with smaller HGM particles have better thermal insulation performance, while composite materials with a HGM diameter of 20 μm have the best thermal insulation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, numerous novel insulation materials have been developed to enhance the energy-conservation performance of the existing and new constructions. These materials provide enhanced thermal-insulation properties [ 7 , 8 , 9 ], enhance economic viability, and promote carbon neutrality. It is clear that the development of high-performance insulation materials that facilitate the reduction in building energy consumption is of paramount significance [ 10 ].…”
Section: Introductionmentioning
confidence: 99%